Nutritional Knowledge, Attitude, and Practices among HIV-positive Individuals in India (Journal of Health, Population and Nutrition, 2013)
This descriptive study investigated the nutrition-related knowledge, attitude, and practices (KAP) among people living with HIV/AIDS (PLHIV) in India. Data relating to nutritional KAP and sociodemographic profile were gathered from a sample of 400 PLHIV from New Delhi, India, using preset multiple-choice questionnaire. The knowledge on HIV/AIDS was low; nutritional knowledge was moderate as 80% of respondents could answer 4 out of 7 questions correctly. The attitude toward disease and food was positive but the application of nutritional knowledge was lacking as indicated by the moderate practice score of 8.1±2.3 out of a total score of 15. There were no significant differences in scores between genders. The PLHIV had knowledge about importance of nutrition during infection, had positive attitude toward the disease and the importance of nutrition during the course of the disease but translation of this knowledge into practice was low. Thus, there is a need for continuous interventions primarily aiming at behaviour change to convert knowledge into healthy dietary practices. J HEALTH POPUL NUTR 2013 Jun; 31(2): 195-201 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16383